Lifetime Maximization Using Grey Wolf Optimization Routing Protocol with statistical Technique in WSNs - Khudor, Baida'a Abdul Qader; Hussein, Dheyaa Mezaal; Kheerallah, Yousif Abdulwahab; Alkenani, Jawad; Alshawi, Imad S. (Informatica, 2023)
Generally, the greatest issue in Wireless Sensor Networks (WSNs) is to make sensor nodes powered by low-cost batteries with limited power last as long as feasible. Thus, energy conservation is an essential topic in WSNs. Since wireless data transmission consumes a substantial amount of energy, the routing mechanism plays a crucial role in preserving the available energy. Consequently, energy-efficient routing methods may save battery power and extend the network's lifespan. Using complicated protocols to properly design data routing may save energy use, but may cause processing delays. This paper offers the Grey Wolf Optimization Routing Protocol (GWORP), extended by using a select optimal path method with detects the statistical best value novel routing mechanism. It is used to discover the ideal route from the source node to the destination (sink) and reuse that path in a manner that ensures energy consumption is evenly distributed across the nodes of a WSN while lowering the time required to find the routing path from scratch each time. Interestingly, GWORP was shown to be more effective than the PSORP (Particle Swarm Optimization Routing Protocol) algorithm in terms of lowering energy usage and minimizing end-to-end latency. The findings also indicate that the network lifespan attained by GWORP might be about 73% longer than that achieved by PSORP.